Hypoplastic right heart syndrome - Weling, Rajaram M.; Narkhede, Nilima A. (International Journal of Contemporary Pediatrics, 2022)
Congenital heart diseases (CHDs) are of two types-acyanotic and cyanotic. Acyanotic heart diseases include atrial septal defect ASD, ventricular septal defect VSD, patent ductus arteriosus PDA, coarctation of aorta and atrioventricular cushion defects. Cyanotic heart disease includes Fallot’s tetralogy, transposition of the great vessels, Total anomalous pulmonary venous return, Tricuspid atresia and single ventricle or hypoplastic left heart or hypoplastic right heart syndrome (HRHS). Hypoplastic right heart is a rarer condition than the hypoplastic left heart. Our patient had a cyanotic heart disease; presented to us with hypoplastic right heart, a very rare association consisting of pulmonary atresia combined with a hypoplastic right ventricle and well-developed pulmonary arteries. Early clinical diagnosis and surgical intervention saved this child.